Latin American Challenges and Recommendations for Poly Adenosine Diphosphate Ribose Polymerase Inhibitor Treatment in Metastatic Castration Resistant Prostate Cancer: An Expert Overview - Rodolfo Borges dos Reis MD, PHD; José L. Aguilar-Ponce MD; Federico Cayol MD, MSc; Angela M. Jansen PhD, MHS; Ray Manneh K MD, MSc; Tomas R Merino MD; Gayatri Sanku PhD, MPH; Laura B. Vaca MD; Pedro Isaacsson Velho MD; Ernesto P. Korbenfeld MD (Cancer Control)
In Latin America, prostate cancer is the third most common cancer overall and the most common in men, with the highest mortality rate of all cancers. In 2022, there were approximately 22,985 new prostate cancer cases and 61,056 deaths from prostate cancer in the region. Patients with metastatic disease that is resistant to cure by castration now have multiple therapeutic options, including poly-ADP ribose polymerase inhibitors. These treatment advances present new challenges, such as developing monitoring protocols for early detection of disease progression to castration resistance. The Americas Health Foundation organized a 3-day meeting with 8 regional oncologists and pathologists to create a paper on metastatic castration-resistant prostate cancer diagnosis and therapy, including the new poly-ADP ribose polymerase inhibitors. The panel examined metastatic castration-resistant prostate cancer in Latin America and recommended ways to improve patient care using published literature and their expertise. Gene mutations play an important role in prostate cancer development. Precision medicine innovations highlight the importance of genotyping DNA variants and tumor biomarkers for targeted treatment. Access to appropriate genetic testing is difficult, medications are available but expensive, and there is a lack of infrastructure and regulatory frameworks that prevent patients from benefiting from innovative therapies. The panel recommends developing a population database and biobank and creating tumor tissue collection, processing, and storage facilities. Multi-stakeholder collaboration is needed to integrate the information gathered, train staff, select target populations, improve patient accessibility, and reduce the cost burden of drugs, genetic counselors, and cancer geneticists in Latin America. Collaboration is essential among healthcare professionals, policymakers, patient advocacy groups, pharmaceutical companies, and international organizations to address these challenges and needs in Latin America.